2009
DOI: 10.1007/s00125-009-1395-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-oil-seed pulses on glycaemic control: a systematic review and meta-analysis of randomised controlled experimental trials in people with and without diabetes

Abstract: Aims/hypothesis Dietary non-oil-seed pulses (chickpeas, beans, peas, lentils, etc.) are a good source of slowly digestible carbohydrate, fibre and vegetable protein and a valuable means of lowering the glycaemic-index (GI) of the diet. To assess the evidence that dietary pulses may benefit glycaemic control, we conducted a systematic review and meta-analysis of randomised controlled experimental trials investigating the effect of pulses, alone or as part of low-GI or high-fibre diets, on markers of glycaemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(216 citation statements)
references
References 59 publications
11
186
1
4
Order By: Relevance
“…This reduction in the AUC of blood glucose concentration after the chickpea treatment calculated was 29 and 36% in Experiment 1 and 2, respectively, compared to bread treatment. These results are supported by others who found reduction in blood glucose response and in AUC after consumption of chickpeas compared to white bread in healthy (Zafar et al 2011;Wong et al 2009;Mollard et al 2011Mollard et al , 2012aHall et al 2005;Keogh et al 2011); or diabetic subjects (Jenkins et al 2012;Sievenpiper et al 2009). However, when fed as chickpea flour or extruded flour supplemented to white bread, no difference was observed for the glycemic effect or subjective appetite compared to the white bread ).…”
Section: Blood Glucosesupporting
confidence: 75%
See 1 more Smart Citation
“…This reduction in the AUC of blood glucose concentration after the chickpea treatment calculated was 29 and 36% in Experiment 1 and 2, respectively, compared to bread treatment. These results are supported by others who found reduction in blood glucose response and in AUC after consumption of chickpeas compared to white bread in healthy (Zafar et al 2011;Wong et al 2009;Mollard et al 2011Mollard et al , 2012aHall et al 2005;Keogh et al 2011); or diabetic subjects (Jenkins et al 2012;Sievenpiper et al 2009). However, when fed as chickpea flour or extruded flour supplemented to white bread, no difference was observed for the glycemic effect or subjective appetite compared to the white bread ).…”
Section: Blood Glucosesupporting
confidence: 75%
“…Whereas increased blood glucose concentration after meals signals satiety and termination of feeding (Mayer 1996). A meta-analysis of 39 trials showed a reduction in the fasting blood glucose, insulin or the markers of glycemic control when pulses were consumed either alone, as a part of high fiber diets or as a low glycemic diet (Sievenpiper et al 2009). …”
Section: Average Appetite and Associations Among The Outcomesmentioning
confidence: 99%
“…Many studies showed their beneficial effects on blood cholesterol, glucose and insulin levels, in addition to prevention of various cancers, such as gastrointestinal, breast and prostate. These properties have been attributed to the unique nutritional composition of the bean that is rich in fibre and phenolic compounds, and low in total fat and saturated fat (Boateng et al, 2008;Karababa, 2006;Marathe et al, 2011;Ranilla et al, 2010;Sievenpiper et al, 2009;Thompson et al, 2008;Wu et al, 2004;Xu & Chang, 2009). The Chinese and Brazilian beans have a similarly high content of dietary fibre (Wu et al, 2004;Costa et al, 2006).…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…A recent randomized clinical trial that utilized three components of the dietary portfolio (nuts, viscous fibres and soyabean protein) has shown that an energy-restricted diet containing these components is more effective than an energy-restricted NCEP-derived diet in reducing blood lipids (48) . Furthermore, although not studied, the dietary portfolio may be effective in management of other chronic diseases such as type 2 diabetes, since there is evidence that viscous fibre and nuts (limited evidence) can improve postprandial glycaemic response acutely and glycaemic control in the long term (49)(50)(51)(52) .…”
Section: Other Benefits and Future Directionmentioning
confidence: 99%